LIMITATION OF THE RIGHT TO PRIVACY BY SECRET OBSERVATION OF THE SUSPECT'S COMMUNICATION (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The right to privacy is one of the fundamental human rights. However, the illumination of modern types of crime (especially organized crime) requires the use of technical achievements that necessarily limit the privacy of the persons to whom these measures have been applied. Thanks to scientific and technological progress, interpersonal contacts take place with the absence of the time distance required to move information from the sender to the recipient. It is realistic to expect that the authority of criminal proceedings can hardly resist the temptation to supplement evidence with the insight into the intimacy of the defendant (or suspect). Thus, achievements of scientific and technological progress are the legacy that makes it easier and adorn human life, but it is also "restless Faust" who is tempting a man at every step. Certainly scientific and technical achievements "provoke" the legislator, as well as the police and judicial authorities in the process of clarifying the criminal case. A delicate task is set before the legislator. The provisions of the law must be such as to provide for the suppression of perpetrators of criminal offenses (especially organized crime), who in the performance of their activities of criminal character use the most modern scientific and technical achievements. On the other hand, a border must be determined, dividing legally from unlawful interference with private life, which must not be crossed by the police and judicial authorities, engaged in the criminal prosecution of perpetrators of criminal offenses.